2021
DOI: 10.1007/s11764-021-01084-w
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health-related care needs among young adult cancer patients and survivors: a systematic literature review

Abstract: Purpose Young adult cancer patients and survivors have age-specific care needs, but care needs related to sexual health are poorly understood. A systematic literature review was conducted to examine sexual health-related care needs among patients/survivors diagnosed with cancer during young adulthood (age: 18–39 years). The prevalence and types needs were assessed along with associated patient factors. Methods Four major databases were screened to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 92 publications
(208 reference statements)
4
60
0
1
Order By: Relevance
“…Albersreported that 80.4% of patients and 37.7% of companions had not received any information in that regard [61]. The results of Lehmann's study likewise showed that the level of sexual health needs had varied between young survivors and other individuals [62]. Therefore, the sexual health care program must become a part of the standard breast cancer care program.…”
Section: Discussionmentioning
confidence: 98%
“…Albersreported that 80.4% of patients and 37.7% of companions had not received any information in that regard [61]. The results of Lehmann's study likewise showed that the level of sexual health needs had varied between young survivors and other individuals [62]. Therefore, the sexual health care program must become a part of the standard breast cancer care program.…”
Section: Discussionmentioning
confidence: 98%
“…Addressing changes in sexual function and their implications for psychosocial and clinical outcomes is essential to quality cancer care; yet, it is often challenging to translate this knowledge into routine practices inclusive of cosurvivors [ 20 , 57 ]. The expected outcomes of this investigation are to (1) characterize sexual function, sexual distress, and dyadic coping of adolescent and young adult CRC survivors and partners through validated measures; (2) provide a deeper understanding of the challenges couples experience as they navigate sexual intimacy after CRC treatment by highlighting the role of interpersonal processes; and (3) use the findings to develop and test interventions supporting the recovery of sexual intimacy of young couples coping with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The expected outcomes of this investigation are to (1) characterize sexual function, sexual distress, and dyadic coping of adolescent and young adult CRC survivors and partners through validated measures; (2) provide a deeper understanding of the challenges couples experience as they navigate sexual intimacy after CRC treatment by highlighting the role of interpersonal processes; and (3) use the findings to develop and test interventions supporting the recovery of sexual intimacy of young couples coping with CRC. Sexual dysfunction and altered intimacy with a partner are salient factors impairing long-term quality of life and emotional well-being [ 20 , 69 , 116 ]. Through the identification of individual, partner, and relationship-level factors that shape how couples negotiate the loss elicited by the illness and redefine their sexual experience or repertoire, this work will inform the development of a couple-based intervention that promotes intimacy by enhancing coping and communication skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations